Spectral Studies of Azo Dye Degradation Using Selected Biofertilizer: Pseudomonas Fluorescens: Life Sciences-Biotechnology for Prospective Medical Science - Sumayya Rehaman; Aravindan G; Karthick G (International Journal of Life Science and Pharma Research, 2022)
Azo dyes are the azo colorants with about 70% dyestuff. Azo dyes persist in the environment for years and are toxic to human life. In the present study, it was attempted to decolorize the selected azodye by three selected biofertilizers: Rhizobium sp., Azospirillum sp. and Pseudomonas fluorescens whereas also to prove biofertlizer’s degradation property. Initially decolorization of 10% azo dye of silk dyeing effluent was biotreated with above mentioned biofertilizers at 37 °C separately as preliminary studies. It was found that preliminarily decolorization of azo dye with Pseudomonas fluorescens with 85% followed by Azospirillum sp. with 74%. Based on this, the percentage decolorization was evaluated for various concentrations of 25, 50, 75 and 100% of azo dye of silk dyeing effluent under static conditions with glucose as carbon source. The percentage decolorization was found to be 91% in 5 days with 25% effluent by Pseudomonas fluorescens reduced to 68% with crude azo dye effluent which had positive influence on the growth of bacterium in the 0.002g glucose as carbon source as growth rate was increased along with decolorization. In contrast the least percentage decolorization was analyzed as 23% in 5 days with 25% effluent by Rhizobium sp. whereas reduced drastically to 11% with 100% effluent. This indicated the dilution is more needed for the better decolorization. The cleavage of azo bond was confirmed through spectral studies such as UV and in HPLC chromatogram of silk dyeing raw industrial bio-treated azo dye Silk dyeing effluent. Microbial growth has utilized and decolorized the dye wastewater shows its biodegradation potential. The high decolorization ability was observed in Pseudomonas fluorescens compared to Azospirillum sp., and Rhizobium sp., as biofertilizer to convert toxic azo dyes into nontoxic compounds reducing the contaminants will prove dual purpose of usage of biofertilizers in the environment.